2017
DOI: 10.1515/environ-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

“The Reality from the Myth”: The poor as main agents of forest degradation: Lessons from Ashanti Region, Ghana

Abstract: The prevailing literature on poverty-environment links mostly presents a rather deterministic view of the nexus between poverty and the environment, revolving around the negative impact of the poor on the environment. Specifically, in Ghana, empirical evidence on the prevalence of forest degradation is sparse because the requisite data are often difficult to obtain. Using a qualitative approach, data collected through in-depth interviews with 45 randomly selected participants and 5 purposively selected key inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…The study findings suggest a positive relationship between land rent and conversion probability from arable land to other land uses such as commercial, industrial and residential land uses, amongst others since the monetary incentive for land influenced arable land conversion decisions of the study participants. Although agriculture is the mainstay of most rural inhabitants in Ghana (GSS 2014a; Abalo et al 2017a;Peprah et al 2017a), and land possession and/or acquisition is deemed a valuable asset among smallholder farmers and individual landowners (Peprah et al 2017b), the current study found contrary evidence among a predominantly agrarian community in which landowners willingly converted their arable land for a price of GH¢400 ($77.00) or more. Adjusted OR Model 2 plus 'the criteria in determining the grounds rent per plot of land' 'reasons for converting original land uses to other uses' and 'observed patterns of land use conversion in the district' Whereas the base amount necessary to change the conversion decisions of the respondents seems 'small', the absolute values in Table 3 portray otherwise (between $19 and $3846).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The study findings suggest a positive relationship between land rent and conversion probability from arable land to other land uses such as commercial, industrial and residential land uses, amongst others since the monetary incentive for land influenced arable land conversion decisions of the study participants. Although agriculture is the mainstay of most rural inhabitants in Ghana (GSS 2014a; Abalo et al 2017a;Peprah et al 2017a), and land possession and/or acquisition is deemed a valuable asset among smallholder farmers and individual landowners (Peprah et al 2017b), the current study found contrary evidence among a predominantly agrarian community in which landowners willingly converted their arable land for a price of GH¢400 ($77.00) or more. Adjusted OR Model 2 plus 'the criteria in determining the grounds rent per plot of land' 'reasons for converting original land uses to other uses' and 'observed patterns of land use conversion in the district' Whereas the base amount necessary to change the conversion decisions of the respondents seems 'small', the absolute values in Table 3 portray otherwise (between $19 and $3846).…”
Section: Discussioncontrasting
confidence: 71%
“…The alternate and 'easy' way out of poverty for most landowners in the study communities are the land rent values offered to usufruct and individual landowners who for the most part, are farmers. Perhaps, solving the poverty problem of the study participants may not necessarily translate into reduction in the sale of arable land in the district considering the recent findings by Peprah and colleagues in Ashanti Region regarding the poor smallholder farmers as agents of deforestation through agricultural extensification (Peprah et al 2017a). Considering the recent increase in the purchase of land and the aesthetic scenery of the study area which mostly serves as a pull factor for prospective land buyers, these occurrences do not augur well for the sustainability of the fragile ecosystem, biodiversity and conservation of the Bosomtwe basin where pristine forest resources are destroyed in the conversion process.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Ghana has embarked on several forest governance approaches to reduce by 45% of all emissions that emanate from the cocoa landscape [56], it is still fraught with widespread D&FD challenges in the high forest zones, including the forests reserves [57][58][59][60]. This review study applies the DPSIR framework to provide information, discuss and analyse the multiple direct and underlying causes of D&FD in Ghana.…”
Section: Resultsmentioning
confidence: 99%
“…The first postulates that poverty is a key factor behind environmental degradation, particularly in developing countries [69,70 page 2170; also see 6,23,7,8,9,10,28,29,30,31,32, 33,34,35]. This predominate approach argues that in order for policy makers to address environmental issues, they must first analyse and give priority to tackle the poverty issues [71 ] and is evidenced in the Bruntland Report [72], World development Report [28] and also discussed more carefully in Perrings [73,74].…”
Section: Differing Approaches To the Poverty-environment Nexusmentioning
confidence: 99%
“…Instead of poverty being the primary culprit leading to increased environmental problems, one counter approach suggests that other factors particularly wealth, greed and power are responsible for environmental degradation in less developed countries. For example, some researcher such as Duraiappah [70]; Boyce [107]; Nunan, [45]; Ahmed [96]; Peprah P, [71]; Olinto P, [22], describes this approach as one that views the exploitative practices of the rich as the primary factor forcing segments of the population into poverty, and in turn exacerbating environmental degradation.…”
Section: Three Theorizations Of the Poverty-environmental Degradationmentioning
confidence: 99%